2014
DOI: 10.11606/issn.1806-6976.v10i1p35-41
|View full text |Cite
|
Sign up to set email alerts
|

Perfil e padrão de uso de crack de crianças e adolescentes em situação de rua: uma revisão integrativa

Abstract: Foi realizada revisão integrativa da literatura para reunir informações sobre o perfil e padrão de uso de crack de crianças e adolescentes em situação de rua. Foram selecionados 19 artigos em bases internacionais, publicados entre os anos 2000 e 2010. Encontrou-se que o uso é de padrão prejudicial, frequente, principalmente em famílias disfuncionais, em fragilidade social, em contextos de violência e exclusão, utilizando-se múltiplas drogas e sofrendo agravos, destacando-se doenças sexualmente transmissíveis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
5
0
3
Order By: Relevance
“…Adolescent users are very vulnerable and easily influenced by groups of friends, as they have a greater need to search for the unknown, the exacerbation of curiosity and the contradiction of values established by family members. 29 Peers are considered important to determine the initiation and continuity of drug use by adolescents, the appreciation of non-parental ties and the establishment of peer bonds intensify, especially when there are family conflicts. In a way, peers contribute to the process of independence, become role models, exert social pressure and influence behavior, becoming important people for the adolescent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescent users are very vulnerable and easily influenced by groups of friends, as they have a greater need to search for the unknown, the exacerbation of curiosity and the contradiction of values established by family members. 29 Peers are considered important to determine the initiation and continuity of drug use by adolescents, the appreciation of non-parental ties and the establishment of peer bonds intensify, especially when there are family conflicts. In a way, peers contribute to the process of independence, become role models, exert social pressure and influence behavior, becoming important people for the adolescent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the court orders caused by drug abuse, there are also clinical health problems. The literature shows that psychiatric comorbidities diagnosed in crack users and multiple drugs are frequent [20][21][22][23][24][25][26][27][28][29][30][31][32][33] , which is an aggravating factor, especially in reports of suicide attempts. 20 Research that investigated the profile of drug addicts undergoing treatment in a psychiatric hospital in the metropolitan region of Curitiba City found that, before starting treatment, 99.4% of a total of 350 individuals had daily drug use.…”
Section: Discussionmentioning
confidence: 99%
“…A large quantitative study by Ferreira, Nogueira Jr., and Costa (2010) showed that the more children attended school, the younger they were, and the less time they spent on the street or worked. Other studies reported youth to find their return to education necessary to meet their life goals (e.g., Cirino & Alberto, 2009;Claro et al, 2014). Cruz and Assunção (2008) concluded that the family and local community contribute to children's engagement in street work, resulting in increased exposure to violence and reduced motivation for schooling.…”
Section: Negative Correlation Between Street Life and Schoolingmentioning
confidence: 99%
“…Desta forma, o papel das famílias no processo de recuperação do paciente, assim como de adoecimento, é considerado muito importante, uma vez que a mudança familiar favorece a individual e vice-versa (Costa, 2010). É com base nesta concepção que, cada vez mais, são elas alvo de intervenção das equipes de saúde da atenção primária, que as veem como aliadas fundamentais e indispensáveis no tratamento do paciente usuário de drogas, buscando o cuidado integral do grupo familiar, oportunizando mudanças no grupo e no paciente (Medeiros, Maciel, Souza, Tenório-Souza, & Dias, 2013;Paula, Jorge, Vasconcelos, & Albuquerque, 2014;Paula, Jorge, Albuquerque, & Queiroz, 2014;Claro et al, 2014). Este estudo apresenta autores que utilizam terminologia de abordagens clássicas, como a epidemiologia (fator de risco/ fator de proteção), somados a outros com um enfoque mais globalizado, buscando, por meio da complementaridade, compreender o fenômeno de forma mais integrada.…”
Section: Introductionunclassified
“…Por outro lado, em uma visão sistêmica, considerando a causalidade circular ou reversa, pode se observar que, se o sofrimento causado pelos conflitos familiares favorece o consumo de crack, por sua vez, os problemas com o crack abalam profundamente a família, aumentam a disfunção no grupo e contribuem para o adoecimento deste, ambos se influenciando, portanto, de forma recíproca (Medeiros et al, 2013;Horta, Vieira et al, 2014, Claro et al, 2014.…”
Section: Introductionunclassified